Effect of stallion seminal plasma proteins on in-vitro capacitation of equine spermatozoa - Arangasamy, A (The Indian Journal of Animal Sciences, 2011)
This study was undertaken to see the capacitation response with the group of heparin (HBPs) and gelatin binding (GBPs) stallion seminal plasma proteins. Frozen thawed stallion spermatozoa were incubated with heparin (10 μg/ml) in the presence of HBPs and GBPs @ 20, 40 and 60 μg/ml. The percentage of capacitated sperm was evaluated after the induction of acrosome reaction with progesterone (100 μg/ml) from 0 and 4 h. Significant differences were observed in the percentage of acrosome reacted spermatozoa at 4 h incubation between HBPs treated and control groups. The GBPs treated group showed non significant difference. The highest value of acrosome reacted sperm was seen in HBPs 40 μg, and in GBPs 60 μg. It can be concluded that the addition of HBPs enhanced the capacitation responses, and best dose level was 40 μg of protein in HBPs groups for induction of acrosome reaction.